A comparison of quasi-Z-source inverters and conventional two-stage inverters for PV applications. Issue 2 (3rd April 2017) - Ayad, Ayman; Kennel, Ralph
Abstract : This paper presents a comparative study between the single-stage quasi-Z-source inverter (qZSI) and the conventional two-stage inverter for Photovoltaic (PV) applications based on an filed programmable gate array (FPGA). The comparison is conducted in terms of the voltage stress on the inverter switches, the required active and passive components, the transient and the steady state performances, and the inverters efficiency. The modelling, the theoretical concepts, and the control design for both inverters are presented and discussed. Moreover, the passive components requirement and the inverters losses analysis are introduced. Experimental investigations are conducted to verify the proposed inverter. It is noted that the qZSI shows a lower voltage stress on the inverter switches than the conventional two-stage inverter when the inverter gain up to 2. The results also demonstrate that the transient and the steady state performances of qZSI are comparable with the ones of the two-stage inverter under the same operating conditions. However, the qZSI shows lower THD values which in turn result in a reduced output filter size and cost. Additionally, the efficiency test is done based on calculations and real measurements for both inverters. The results point out that the qZSI shows higher efficiency than the conventional solution. Based on these observations, the qZSI proposes an attractive alternative for PV applications.